Development of a 3D virtual platform for an upper arm robotic exoskeleton - Tageldeen, M.K. (Institute of Electrical and Electronics Engineers Inc., 2017)
Robotic rehabilitation is overtaking traditional rehabilitation, since it ensures exercises are practiced accurately with flexibility in the degree of assistance that the patients require. Nevertheless, robotics rehabilitation is automatic and can become monotonous, hence, disengage the patient. Although Serious Games are an excellent approach to engaging the patients in robotics rehabilitation with exoskeletons, the lack of a specialty development platform leads game developer to invest a significant amount of time to produce the basic software functionalities of interfacing the hardware and controlling the communication between the different system components. This paper presents a set of interfacial nodes that makes up virtual 3D gaming environment that is based on but not limited to upper limb exoskeletons. The nodes use a combination of accelerometer, gyro, compass and a variable resistance to measure the joints kinematics and interpolates the dynamics, the framework provides functions that models the sensors input and simplify object generation in 3D Serious Games engines. © 2016 IEEE.